Innovative developments: Complex feed concentrates – lizunts; carbohydrate-vitamin-mineral complexes; buffer premixes – deoxidizers - Ishmuratov Kh.G.; Mustafin I.G.; Shakirov Sh.K.; Shiriev V.M.; Garankov I.N. (BIO Web of Conferences)
Animal husbandry of the Republic of Bashkortostan occupies about 94% of the structure of gross agricultural output. The leading industry in the livestock industry of the republic is cattle breeding, which accounts for about 66% of the meat produced. Near the cities, cattle breeding is developing in the meat and dairy direction, in the mountainous and northeastern regions - meat and meat-dairy. The share of pork in the meat balance is about 17%, lamb is about 2%. Forage production is the foundation on which the production of livestock products is based. The main feed products are bulky (coarse and juicy) feed of own production, where the main consumers are ruminants. For a complete and balanced feeding, not only concentrated feeds are needed, but also feed additives that make up for the lack of protein, carbohydrates, vitamins and minerals, prepared with local cheap, affordable raw materials. Such additives developed by the staff experimental station “Ufa” Ufa Federal Research Center of the Russian Academy of Scienc, include complex feed concentrates – lizunts, carbohydrate-vitamin-mineral complexes – salt blocks and buffer deoxidizers to reduce the acidity of the rumen of highly productive cows.